Penerapan Pembelajaran Yang Berbasis Pendekatan Scientific bagi Guru - Dwi Iriyani; Sodiq Anshori (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
This article is the result of community service activities aimed at the improvement of skills ofpartner communities that teachers SMPN 2 Balongbendo bias formulate instructional designappropriate and adequate by the scientific approach and relevant to the local requirements andcan implement an authentic assessment on her students. The benefits of this abdimas activities,among others: (1) Master Junior High School 2 Balongbendo have an understanding of theimportance of design concepts and learning application that is based on a scientific approach;(2) Teachers in Secondary Schools 2 Balongbendo able to use a scientific approach (scientificapproach) in learning; and (3) Teachers in Secondary Schools 2 Balongbendo able toimplement authentic assessment on student competency achievement of students in accordancewith the strategy as well as relevant local requirements. Training and mentoring done bylectures, video screenings, discussion, interactive dialogue, brainstorming and workingpractices. Abdimas overall activities carried out within the period of 7 months.